Overpasses and underpasses: Effectiveness of crossing structures for migratory ungulates. Issue 8 (4th August 2016) - Simpson, Nova O.; Stewart, Kelley M.; Schroeder, Cody; Cox, Mike; Huebner, Kari; Wasley, Tony
ABSTRACT: Maintenance of movement corridors is a fundamental component of the conservation of biological diversity, and is especially critical for terrestrial species that migrate extended distances. Highways and interstate freeways fragment corridors and often result in increased mortality of terrestrial migrants from collisions with vehicles. Wildlife crossing structures are an important tool in multiple ecosystems to allow safe passage for wildlife across roadways. Indeed, crossing structures have been used extensively in Europe and with increasing frequency in North America to reconnect fragmented habitats for numerous species. Few projects, however, have documented responses to >1 structure type simultaneously that are close to one another. We used mule deer ( Odocoileus hemionus ), a widespread species across diverse bioregions in western North America, to test hypotheses about efficacy of 2 different types of crossing structures for ungulates. We documented behavioral responses and use of overpasses and underpasses by mule deer. Our metrics to evaluate success included passage rates and the number of animals that crossed each structure. Crossing structures were used by mule deer immediately following construction and although all of the crossing structures were used, we observed greater passage rates at overpasses than underpasses. Wildlife crossing structures reduced habitat fragmentation and enhanced connectivity by allowing safe passage across US 93. More importantly, those structures succeeded in removing a large number of mule deer from the roadway making US 93 safer for wildlife and motorists. © 2016 The Wildlife Society.